Liesl & Po - Oliver, Lauren, 1982-; Acedera, Kei (New York : Harper, 2011)
A mix-up involving the greatest magic in the world has tremendous consequences for Liesl, an orphan who has been locked in an attic; Will, an alchemist's runaway apprentice; and Po, a ghost, as they are pursued by friend and foe while making an important journey.
MSBA Nominee 2012-13.
Keywords: Magic -- Juvenile fiction; Ghost stories; Orphans -- Juvenile fiction; Future life -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Fantasy fiction